Antioxidant Bioactive Peptides from By-Product Canned Yellowfin Tuna (Thunnus sp.) through an Enzymatic Membrane Reactor (EMR) - Hardoko, Hardoko; Priantono, Azahraa K.; Reda, Flavia D.; Haji, Tunggul S.; Sitanggang, Azis B.; Puspitasari, Yunita E. (:Agency for Marine and Fisheries Research and Human Resources, Indonesia, 2025)
As a by-product of the pre-cooking phase, canned yellow fin tuna (Thunnus sp.) is processed into body juice. A bioactive peptide derived from an organism#39;s body juice was developed to create a functional food. Hence, the purpose of the research was to evaluate the biological activity of antioxidant bioactive peptides prepared from body juice. Three stages were conducted to determine the substrate-to-enzyme and enzyme-to-substrate ratios for the production of antioxidative bioactive peptides in a batch reactor. These stages include the production of antioxidative bioactive peptides in an automated EMR with a constant flux and residence time, as well as the production of bioactive peptides using ultrafiltration with membranes of 10, 5, 4, and 2 kDa. The process was conducted at a temperature of 50°C, pH level of 7, constant flux of 8.08 L/m 2 /h, enzyme concentration of 15%, and substrate concentration of 2%. Furthermore, the optimal treatment implemented an automated EMR and filtered through a membrane of size 4 kDa, generating an IC 50 value of 0.604 mg/mL for antioxidant activity. The LC–MS analysis results indicated that the bioactive peptide, which passed through a 4 kDa membrane, contained the amino acid phenylalanine. Therefore, it can be inferred that an automated EMR could potentially be applied to create bioactive peptides from the body juice of by-products of canned yellow fin tuna (Thunnus sp.) that exhibit antioxidant activity.